Building fires in the snow : a collection of Alaska LGBTQ short fiction and poetry - Amore, Martha; Childs, Lucian (University of Alaska Press, 2016)
"Diversity has always been central to Alaska identity, as the state's population consists of people with many different backgrounds, viewpoints, and life experiences. This book opens a window into these diverse lives, gathering stories and poems about lesbian, gay, bisexual, transsexual, and queer life into a brilliant, path-breaking anthology. In these pages we see the panoply of LGBTQ life in Alaska today, from the quotidian urban adventures of a family--shopping, going out, working--to intimate encounters with Alaska's breathtaking natural beauty. At a time of great change and major strides in LGBTQ civil rights, Building Fires in the Snow shows us an Alaska that shatters stereotypes and reveals a side of Alaska that's been little seen until now"--